(untitled) (Journal of Management, 2020)
The paper focuses on the sales, liquidity and profitability analysis in corporate finance. Any firm aims to maximize its earnings per share. However, most of the firms try to attain maximum profit. In this way, this study is initiated to find out the cause and effect relationship between sales, liquidity and profitability. The study is concentrated on the cement industry in Nepal for four year’s data. The quantitative research design has been used to draw a valid conclusion. The descriptive statistics, correlation analysis and regression analysis were used in the analysis of the sample and there is any relationship among sales, liquidity and profitability in the cement industry in Nepal. The study found a significant positive relationship between sales and profitability, similarly insignificant positive relation between net working capital and profitability.